2020
DOI: 10.1016/j.dss.2020.113359
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous proposal evaluation problem

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Amankwah-Amoah (2020), Farmaki et al (2020), Singh and Crisafulli (2020), Asadabadi and Zwikael (2020) Green "consumer behavior", "costs", "dynamic pricing", "economics", "game theory", "industry", "pricing", "profitability", "purchasing", "quick response", "revenue management", "sales", "strategic behavior", "strategic consumer behavior", "strategic consumer behaviors"…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amankwah-Amoah (2020), Farmaki et al (2020), Singh and Crisafulli (2020), Asadabadi and Zwikael (2020) Green "consumer behavior", "costs", "dynamic pricing", "economics", "game theory", "industry", "pricing", "profitability", "purchasing", "quick response", "revenue management", "sales", "strategic behavior", "strategic consumer behavior", "strategic consumer behaviors"…”
Section: Resultsmentioning
confidence: 99%
“…These effects, however, diminish upon the appearance of another crises event. Asadabadi and Zwikael (2020) discuss about unethical suppliers who introduce uncertainty without considering customers' requirements. Thus, suppliers introduce ambiguity in such critical areas as new technologies and strategic misrepresentation.…”
Section: Strategic Responses To Crisismentioning
confidence: 99%
“…In many cases, the presence of complex criteria contradictions and ambiguous situations in the hierarchy model could impact the result of the decision-making process [64]. As the number of criteria involved in the hierarchy increase, evaluators could be confused, leading to difficulties in clearly comparing some proposals due to ambiguity.…”
Section: Construction Of Hierarchymentioning
confidence: 99%
“…Saaty [44] proposed that AHP provides the objective mathematics to process the inescapably subjective and personal preferences of a group in making a decision. AHP is considered one of the most popular and powerful multicriteria, decision-making methods [45,46], which is a suitable method to more objectively obtain the weight of the indexes [47]. Lu et al [48] demonstrated how a particular company can decide on which strategic marketing orientation to adopt based on AHP.…”
Section: System Performance Weighted Rankingmentioning
confidence: 99%